Enhancement of energy efficient cluster based data gathering protocol for wireless sensor networks - Muhammad Faheem, 1986-; Md. Asri Ngadi; Fakulti Sains Komputer dan Sistem Maklumat (2012)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2012